The Influence of Reading Health News on Online Portals on the Healthy Lifestyle of Students in the Faculty of Medicine and Health Sciences at UIN Alauddin Makassar - Syamsidar, Syamsidar; Firdayanti, Firdayanti (Jurnal Mercusuar, 2021)
"The development of a growing lifestyle sometimes overlooks health as a fundamental thing, starting from junk food, makeup, and so on. On the other hand, the presence of online health news portals also comes in the form of education that helps to understand more about a better way of life, but how significant is the influence of reading news in relation to a healthy lifestyle. This research shows that the online health news portal on a healthy lifestyle is important, often visited 3-5 times a day. Many respondents who use the online portal are Alodokter, Scholar, and Infokesehatan.com. Of the 290 respondents based on gender, the majority are women (90%) with an average age of 18-22 years. The highest intensity of respondents' answers is reading health news on online portals for <3 hours a day. And in terms of attention, reading health news on online portals has an impact on the healthy lifestyle of FKIK UIN Alauddin Makassar students.